XIth International Congress on Thrombosis and Haemostasis 1987
DOI: 10.1055/s-0038-1644285
|View full text |Cite
|
Sign up to set email alerts
|

Protein C and Protein S in Mild and Moderate Preeclampsia

Abstract: In normal pregnancy, total protein S antigen and activity have been reported to be markedly reduced, whereas protein C level was found unaltered. In contrast, in severe preeclampsia protein C antigen was found to be considerably reduced. The presentstudy was done to clarify whether similar changes in protein Cwould alsobe observed for the mildand moderatepreeclamptic state andwhether there would be any effects on the level ofprotein S, since nodata on this cofactor in preeclampsia have been reported to date. 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This contradicted the findings of Saleh et al (29) who reported elevated (3-TG in preterm labor when compared to normal term labor. Protein C was found to be unaffected in normal pregnancy (30,31 ) and total protein S antigen and activity were reported to be markedly reduced (31,32), as similar in this study during labor in normal pregnancy, PIH, and GDM.…”
Section: Discussionsupporting
confidence: 82%
“…This contradicted the findings of Saleh et al (29) who reported elevated (3-TG in preterm labor when compared to normal term labor. Protein C was found to be unaffected in normal pregnancy (30,31 ) and total protein S antigen and activity were reported to be markedly reduced (31,32), as similar in this study during labor in normal pregnancy, PIH, and GDM.…”
Section: Discussionsupporting
confidence: 82%